Prediction of Sediment Yield from the Bandi Catchment Using Morphometric Characteristics - Singh, Surendra; Sharma, K D (Annals of Arid Zone, 2016)
Morphometric characteristics of different drainage basins, their interrelationship and regression analysis for the prediction of sediment yield from the Bandi catchment have been highlighted in this paper. The regression analysis of sediment yield with different morphometric characteristics showed that the sediment yield from different drainage basins could be predicted by constant of channel maintenance, followed by relief ratio and drainage density.